Analisis Kritis Pasal 156 (C) KHI Mengenai Pemindahan Hak Asuh Anak dalam Konteks Penelantaran oleh Ibu: Perspektif Maqāshid Al-Syarī’ah - Mitra Kurniawan; Zulfahmi Bustami; Sofia Hardani (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – This study aimed to perform a critical analysis of Article 156 (c) of the Indonesian Compilation of Islamic Law (KHI), which exhibited a legal loophole. The article failed to clearly and unequivocally address the situation where the mother might be capable of caring for the child but the father, despite having the means, refused to provide support. Consequently, in cases where the mother lacked sufficient income, the child could be left abandoned. Methods – This research falls under the category of literature review within the field of Islamic studies, employing a qualitative normative approach. The methodology utilized for data processing and drawing conclusions was content analysis. Findings – The findings of the study underscored the necessity of examining the aforementioned issues through the lens of maqāshid al-syarī'ah, as they are intricately linked to the question of whether the mother's custody should be upheld or if it is more beneficial to transfer it to the party with similar custodial rights. This perspective is crucial as it considers the overarching objectives and principles of Islamic law, guiding the decision-making process towards outcomes that align with the broader aims of justice, welfare, and protection of the child's best interests. Research implications –The theoretical implications encompass the potential expansion of concepts and legal thoughts in Islamic law concerning the protection of children's rights, and provide a foundation for critical reflection on existing legal frameworks. Thus, the research findings may aid in the development of a more inclusive theory of Islamic law that aligns with principles of humanity and justice. Top of Form Originality/value – This study addresses a notable gap in Indonesian Islamic law concerning child custody rights, specifically regarding maternal abandonment. By critically analyzing Article 156 (c) of the Indonesian Compilation of Islamic Law (KHI), the research identifies a legal loophole affecting children's welfare when mothers lack sufficient support. Unlike previous studies, this research integrates maqāshid al-syarī’ah principles, offering a comprehensive perspective.